Competitiveness, subsidiarity, and industrial policy - Devine, P. J.; Katsoulacos, Y. S., 1953-; Sugden, Roger (Industrial economic strategies for Europe., 1996)
What does competitiveness mean? In recent years, discussion of economic policy has become dominated by the notion of competitiveness. In this volume a group of leading economists explore the issue through cross-country comparisons and by means of single country case studies. They also examine: * the relationship between competitiveness and community objectives * the co-existence of diversity, subsidiarity and EU industrial policy * the impact of European enlargement and further integration.